1980
DOI: 10.1111/j.1432-1033.1980.tb04286.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Effect of Ammonium Chloride on Nitrogen Fixation by Azotobacter vinelandii and by Bacteroids of Rhizobium leguminosarum

Abstract: 1. Evidence is presented that the direct depressing effect of ammonium chloride on nitrogen fixation by Azotobacter vinelandii is due to inhibition of the electron transport system to nitrogenase. Furthermore, we were able to confirm the observation [Houwaard, F. (1979) Appl. Environ. Microbiol. in the press] that ammonium chloride has no short-term effect on nitrogen fixation by isolated bacteroids of Rhizobium leguminosarum.2. By means of the flow dialysis technique it could be demonstrated that in A . vine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
2

Year Published

1985
1985
2002
2002

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(62 citation statements)
references
References 47 publications
2
58
2
Order By: Relevance
“…vinelandii is known to at least partially switch off nitrogenase activity when exposed to a sudden increase in the concentration of ammonium (14). In contrast to the oxygen stress and in agreement with a previous report (23) a slight increase in the cellular ATP pool could be observed under the conditions of the present investigation.…”
Section: Resultscontrasting
confidence: 43%
“…vinelandii is known to at least partially switch off nitrogenase activity when exposed to a sudden increase in the concentration of ammonium (14). In contrast to the oxygen stress and in agreement with a previous report (23) a slight increase in the cellular ATP pool could be observed under the conditions of the present investigation.…”
Section: Resultscontrasting
confidence: 43%
“…(a) NH3 could have a direct effect on nitrogenase, on the ATP supply for nitrogenase, or on the electron transfer system to nitrogenase (8). However, a direct effect of NH3 on nitrogenase activity seems unlikely.…”
Section: Resultsmentioning
confidence: 99%
“…In Azotobacter vinelandii, it was observed that the addition of NH 4 ϩ to N 2 -fixing cells rapidly inhibits nitrogenase activity by decreasing the flow of reducing equivalents, whereas at high concentrations it also reduces the intracellular ATP/ADP ratio (92). In contrast, addition of NH 4 ϩ does not affect nitrogenase activity of isolated SBs of R. leguminosarum, which are instead unable to take up NH 4 ϩ actively, and therefore it was concluded that NH 4 ϩ could affect the energized state of the membrane only when it is taken up (92). The amtB-mediated negative effect on BT growth supports the notion that, unlike free-living diazotrophs, BTs are programmed not only to fix N 2 but also to release most of the N fixed and that the N 2 fixation process in BTs is regulated to satisfy the plant requirement for N.…”
Section: Downregulation Of Nhmentioning
confidence: 99%
“…Addition of NH 4 ϩ (and NO 3 Ϫ ) also inhibits nitrogenase activity, possibly not directly but after conversion to glutamine, or through the regulation of a plant function (173), e.g., the reduction of the O 2 or C supply by the plant (15). In fact, it has been shown that isolated SBs do not take up NH 4 ϩ and that SBs in the nodule do not express the amtB gene, which is required for high-affinity NH 4 ϩ uptake activity (92,179). Moreover, externally added NH 4 ϩ may never reach the SBs, since the NH 4 ϩ -assimilating enzymes are highly expressed in the cytoplasm of ICs.…”
Section: Nhmentioning
confidence: 99%
See 1 more Smart Citation